Rodent Stroke Model Guidelines: An Update - Tripathi A.K.; Singh R.S.; Soni A.; Tripathi R.; Patnaik R. (My University, 2025)
According to a recent statistical report from the American Heart Association (AHA), stroke is the fifth major reason for mortality and morbidity. Stroke is a devastating clinical condition for which efficient interventions are not currently available. The rodent stroke model has critical significance in a series of preclinical tests for neuroprotection, neurotransmitters, and neuroplasticity studies. Despite using animal modeling in neuroprotective research, their modeling, development, and preclinical evaluation of animals have been rarely and consistently demonstrated. Comorbidities like aging, diabetes, hypertension, and smoking are major contributors to stroke and the use of comorbid rodent models of stroke is clinically relevant to the human disease condition. Animals, like hypertensive rats and diabetic mice, these comorbid models, are used to explore the pathophysiology of cerebral stroke. Regional cerebral blood flow (rCBF) real-time tracking of arterial blood flow by using laser Doppler flowmetry (LDF) provide evidence for the success of middle cerebral artery (MCA) occlusion. Several factors play an important role in neurological outcomes, while have not happened before effectively addressed in Stroke Therapy Academic Industry Roundtable (STAIR) recommendations. Here, we describe the general guiding principle for a preclinical stroke model, STAIR committee recommendation, the procedure to develop intraluminal Middle Cerebral Artery Occlusion (MCAO) in rodent, surgical procedure optimization, MCA occluders like silicone-rubber coated, nylon coated, nail-polish coated, methyl methacrylate coated, poly-L-Lysine (PLL) coated and resin-coated and their physical properties. Besides, we will provide information on neurobehavior assessment, neuroprotection by volatile anesthesia molecule (halothane, isoflurane, desflurane, sevoflurane, and ketamine/xylazine cocktail), hypothermia induced neuroprotection, and hyperthermia damaging effect on ischemic injury. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.